2020
DOI: 10.2334/josnusd.20-0065
|View full text |Cite
|
Sign up to set email alerts
|

Shear bond strength and interfacial analysis of high-viscosity glass ionomer cement bonded to dentin with protocols including silver diammine fluoride

Abstract: Purpose: High-viscosity glass ionomer cements (HV-GICs) are reinforced with ultrafine, highly reactive glass particles, as well as a higher-molecular-weight polyalkenoic acid component. Silver diammine fluoride (SDF) is an agent with promising activity against active caries. The present study aimed to evaluate the shear bond strength (SBS) and interfacial morphology of a new HV-GIC bonded to dentin after treatment with various adhesive protocols including SDF. Methods: HV-GIC cylinders were bonded to dentin af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…On the other hand, François et al founded that no significant differences in SBS for EQUIA Forte bound to sound dentin using SDF [26].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, François et al founded that no significant differences in SBS for EQUIA Forte bound to sound dentin using SDF [26].…”
Section: Discussionmentioning
confidence: 99%
“…In 2021, Eslami et al proved that one or two applications of SDF followed by GIC coverage could remineralize advanced dentin caries in the presence of artificial saliva [ 82 ]. Other studies stated that SDF did not affect the shear bond strength of GIC with sound dentin [ 83 ] or carious dentin [ 84 ] and could improve the resistance of GIC to secondary caries [ 83 ]. A systematic review and meta-analysis concluded that a prior application of SDF did not weaken the bonding of GIC to dentin [ 85 ].…”
Section: Gic Restoration In Conjunction With the Application Of Sdfmentioning
confidence: 99%
“…The sample size was calculated using Open-epi software, considering the lowest mean shear bond strength values of 9.98 ± 3.15 [13], with a confidence interval of 95% and margin of error 5%. The power of test was 80%.…”
Section: Sample Size Calculation and Groupingmentioning
confidence: 99%